(untitled) (Research, Society and Development, 2024)
Introduction: In this study, the absorption lines and emission lines of magnetic spectral energy are analyzed in comparison with Ying and Yiang energy through the application of needles at points P5 and P9 on the light meridian. Material and method: In this treatment, 20 volunteers were selected for the experiment, in a period of 30 and 10 minutes in two different groups, scoring points P5 and P9 in each group. In the first group, the acupuncture points do not coincide with the spectral lines and in the second group, the acupuncture points coincide with the spectral lines (capture points and energy emission points). It was measured by the thermograph, the measuring distance is 10 cm, as temperature images in the circulation meridians. Result: There is a statistically significant mean difference between the moments in both patients with a time of 30 minutes and a time of 10 minutes, in both groups. The temperature in both dangerous groups, as in Group 1 where the average dropped from 33.87 to 32.64 (p-value = 0.022). In group 2 the differences are much greater, generally 2 points, in which the p-value is 0.003. In the median, the difference was also 2 points from group 2 to group 1. The p-values were considered important considering the level of significance adopted. Conclusion: At all times a decrease in temperature is observed, however when the stimulated acupuncture points coincide with the spectral lines, the drop in temperature is more significant.